Perubahan kadar hemoglobin postmortem pada tikus putih galur Sprague-Dawley - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Beta Ahlam Gizela - Postmortem hemoglobin concentration changing in Sprague-Dawley white mouse Background: Postmortem changes in a death body have a lot of purposes, one of them is predicting the time of death. The common method used to predict the time of death is by detecting hypostasis, rigidity, decreasing temperature, and decomposition. Objectives: To find out postmortem hemoglobin concentration changing pattern. Methods: This research is a preliminary study. We used Quasi Experimental Design. The subjects were 31 white male mice aged of two months old. The mouse blood was taken in a periodic time: antemortem, 0, 1, 2, and 3 hours postmortem, and hemoglobin concentration was examined using Sahli method. Results: Data taken from this research were analyzed by regression analysis and t-test. The result showed that postmortem hemoglobin against time pattern was a curve. The hemoglobin concentration is significantly decreased in the first hour (p0.05). There was no significant difference between antemortem and 0 hour postmortem (p>0.05). There was a significant difference between antemortem and 1, 2, and 3 hours postmortem (p